EP1340 Excision of paraaortic bulky disease in a patient with advanced ovarian cancer after treatment with 3 cycles of neoadjuvant chemotherapy. (1st November 2019) - Mitsopoulos, V; Biliatis, I
Abstract : Introduction/Background: A 55 year old patient presented with advanced ovarian cancer with disease at the mediastinal lymph nodes, the right diaphragm, the omentum and a 7 cm lymph node block at the paraaortic area. The MDT decided to commence with neoadjuvant chemotherapy taking into consideration the mediastinal lymoh nodes. She had 3 cycles of carbo/taxol. On post chemo CT scan she had complete response at the chest and partial response intraperitoneally. Thus, We decided to offer interval debulking surgery. Methodology: In this video monopolar diathermy is uded to excise bulky disease from the paraaortic area after mobilising the duodenum Results: She underwent liver mobilisation and right diaphragmatic excision, en-block resection of the spleen and omentum, excision of disease from the paraaortic area and stripping of pelvic peritoneum Conclusion: Excision of disease from the paraaortic area after chemotherapy is feasible and should be offered in patients with advanced ovarian cancer in the setting of interval debulking surgery Disclosure: Nothing to disclose